Gold-ligand interaction studies of water-soluble aminoalcohol capped gold nanoparticles by NMR - Porta, Francesca (Langmuir : the ACS journal of surfaces and colloids, 2008)
Novel reproducible preparations of gold nanoparticles capped by aminoalcohols have been set up by reduction of HAuCl4 with NaBH4 in aqueous solution. The characterization of Auaminoalcohol nanoparticles performed by 1H NMR, ATR-FTIR, UV-vis spectroscopies, and TEM microscopy highlighted the binding site and the nature of the Au-NH bond